2017
DOI: 10.1186/s12885-017-3320-7
|View full text |Cite
|
Sign up to set email alerts
|

Transhepatic arterial infusion chemotherapy using a combination of miriplatin and CDDP powder versus miriplatin alone in the treatment of hepatocellular carcinoma: a randomized controlled trial

Abstract: BackgroundBased on promising results from a Phase I study of hepatic arterial infusion chemotherapy using a combination of miriplatin and cisplatin powder (DDP-H) for unresectable hepatocellular carcinoma (UMIN-CTR000003541), a multicenter, open-label, randomized phase II study was conducted to evaluate the efficacy and safety of the combination therapy versus miriplatin monotherapy.MethodsNineteen patients, five and fourteen Barcelona-Clinic Liver Cancer staging classification A and B cases, respectively, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Kamimura et al demonstrated a randomized trial for evaluating the effect of TAI using combination of miriplatin and cisplatin versus miriplatin alone. 37 They reported that the combination therapy of miriplatin and cisplatin had significantly better progression-free survival and overall DCR. Recently, as miriplatin has become the standard drug in addition to anthracyclines in TACE in Japan, [38][39][40] the results of the present study also provide useful basic information whether to add TAI using cisplatin to TACE using miriplatin in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Kamimura et al demonstrated a randomized trial for evaluating the effect of TAI using combination of miriplatin and cisplatin versus miriplatin alone. 37 They reported that the combination therapy of miriplatin and cisplatin had significantly better progression-free survival and overall DCR. Recently, as miriplatin has become the standard drug in addition to anthracyclines in TACE in Japan, [38][39][40] the results of the present study also provide useful basic information whether to add TAI using cisplatin to TACE using miriplatin in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Although various chemotherapeutic agents have been used for treating HCC[ 16 , 17 ], platinum agents achieved a better response rate in a multicenter phase II study enrolling patients with unresectable HCC[ 29 ]. Based on these results and the fact that miriplatin showed no cross-resistance with different generations of platinum agents[ 30 ], we conducted a phase I study[ 18 ] and a phase II study[ 19 ] of combined therapy with miriplatin-TOCE and DDP-H-HAIC and demonstrated its safety and efficacy for patients with unresectable HCC. In fact, we could repeat the miriplatin-TOCE/DDP-H-HAIC combination therapy for the two cases in the present study without severe adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a phase I study of the combination therapy and determined that both miriplatin and DDP-H can be administered up to the maximum tolerated dose of each drug without additional adverse effects[18]. Along with these results, we conducted a phase II study and confirmed the efficacy and safety of the combination therapy in cases with multiple HCC[19]. Here, we report two cases of patients with unresectable HCC who were successfully treated by miriplatin-TOCE/DDP-H-HAIC combination therapy, resulting in complete responses with no significant adverse events.…”
Section: Introductionmentioning
confidence: 99%